Epidemiology and Ideology: Why health equity is problematic in the United States - Cynthia R Hall (University of North Florida, 2019)
Health and healthcare are central elements to the achievement of social justice. Braveman and Gruskin are proponents of health equity as a means to realize social justice. They define health equity as the "absence of systemic barriers to health" that are derived from the unequal power, influence, and capital of marginalized groups within societies (2003, p. 254). John Rawls and Norman Daniels have theorized that social justice requires a fair distribution of goods in a society and that good health is of moral importance to this effort, respectively. Thus, having fair access to a healthy life is a crucial element in the attainment of a just society. However, social justice, achieved through fair access to good health, is made problematic in the United States. Specifically, in the United States, epidemiology is guided by traditional standards of scientific methodology requiring proof to a high degree of certainty. This standard often neglects social factors that may be as relative to causation as readily discernable factors. Social factors that affect health may be invisible or hidden within structural elements of society. In the United States, these structural components are often influenced by America's historic imperialistic ideology that serves to preference the dominant culture over "others." Given traditional scientific notions of causality and predominant American ideology, structural issues relative to health inequity are often discounted or demoted as causal elements, making the realization of social justice elusive.